Hubungan antara efikasi kendiri dan keresahan terhadap motivasi pembelajaran dalam talian dalam kalangan pelajar ijazah sarjana muda - Anuar, Ainol Hakim (2021)
The COVID-19 pandemic that hits the country resulted in the shifting of learning methods of among higher education students from physical encounters in the classroom to the implementation of online learning. This study aims to examine the relationship between self-efficacy and anxiety towards motivation among undergraduate students of the Faculty of Social Sciences and Humanities (FSSH) at Universiti Teknologi Malaysia (UTM) Johor. There are few studies have been conducted to look into simultaneous relationship between three variables in the context of higher education students who are taking online learning. This study uses a correlation design and involves three questionnaire instruments which are Self- Efficacy Questionnaire for Online Learning (SeQoL), Anxiety Scale Item and Academic Motivation Scale (AMS). A total of 306 undergraduate students consisting of year 1 until 4 FSSH were involved in this study. Descriptive analysis shows that the students involved in this study have moderate level of self-efficacy, low level of anxiety and moderate level of motivation towards online learning. Meanwhile, Spearman correlation analysis showed self-efficacy had a significant positive highly moderate relationship with (r = 0.601) towards motivation. While the anxiety had a significant relationship negative weak relationship with (r = -0.390) towards motivation. The multiple regression analysis that are conducted showed self – efficacy (ß = 0.615, p < 0.05) contributed 37.6% (r = 0.615) to the change in variance on motivation [F (1, 304) = 184.512, p < 0.05]. While self-efficacy and anxiety produced a result (ß = -0.237, p < 0.05) which contributed 42.1% (r = 0.652) change in variance on motivation [F (2, 303) = 111.998, p < 0.05]. This study has implications especially for management of institutions of higher learning (HEIs), lecturers and students of HEIs in order to help students maintain a high level of selfefficacy as well as under control of anxiety in order to increase motivation for online learning. Several suggestions have also been put for further studies in future in order to help students stay motivated while engaging online learning during the COVID-19 pandemic.